Evaluation of Waste Management Performance in Pariaman City Using Life Cycle Assessment (LCA) - Paramita, Dian; Aziz, Rizki; Indah, Shinta (CIVED, 2023)
Pariaman City's waste generation in 2022 is 38.26 tons/day. Waste management in Pariaman City is still not optimal, resulting in waste piling up in TPA South Tungkal. The waste reduction value at the research location after processing with BSF larvae can reduce 0.005 tons/day or 0.02% of the total waste generation in Pariaman City. The environmental impacts in waste management studied are Global Warming Potential (GWP), Acidification Potential (AP), and Eutrophication Potential (EP). Reducing the environmental impact of processing organic waste has been carried out, the smallest impact reduction results were obtained, namely in scenario 1, namely processing organic waste with BSF larvae in waste banks and TPS 3R. The results obtained were the impact characterization value from comparing several impact categories. GWP value 32,060,838.136 103 kg CO2-eq, AP 0.00246 x103 SO2-eq, and EP 0.00134 x103 kg PO4-3. So it can be concluded that scenario 1 has a smaller GWP, AP, and EP impact on the environment compared to scenario 0 and is used as the best alternative scenario for waste management in Pariaman City